Wakaf Keluarga Perspektif UU No. 41 Tahun 2004 dan Maqasid Al-Usrah Jamal Al-Din Atiyyah - Arif Zunaidi (Institut Agama Islam Negeri (IAIN) Kediri, 2021)
Waqf is part of Allah’s command for those who have excess wealth. The rewards of waqf will continue to flow even after the perpetrator dies, as long as the waqf benefits others. In its development there are two categories of waqf, namely family waqf (dzurri) and khairi waqf. Family waqf is related to benefits intended for nasab or families and their descendants. Several countries have removed this type of waqf practice because it is considered not to provide benefits to the general public, because it focuses on the family only. In fact, waqf should be one way to improve the people’s economy because it is included in the Islamic philanthropy section. This study used qualitative research methods. This method provides an overview and describes several findings in the field, especially in this study related to the practice of family waqf in Indonesia. As a result, Dzurri waqf was recognized with the promulgation of Law no. 41 of 2004 concerning Waqf. However, in terms of management, the rules are still unclear. So prone to conflict. To reduce conflict, the Waqf Pledge Deed must clearly contain nazhir and mustahik. It is recommended that management be carried out productively in order to provide more benefits for mustahik. While the dzurri waqf in the view of maqasid al-usrah Jamal Al-Din Atiyyah includes three things, namely Hifz tadayyun fi al-usrah, Tandzim Al-Janib Al-Mali Li Al-Usrah, Tandzim Al-Janib Al-Mu’Assati Li Al Usrah.